Assistive and Rehabilitation Engineering - Rybarczyk, Yves (IntechOpen, 2019)
Rehabilitation enables people with sensorimotor and cognitive disabilities to regain functions and autonomy. However, over the past few years, there has been a reduction in healthcare providers to assist patients. Fortunately, this decline has been accompanied by an increase in technological applications to support health systems. This new paradigm brings promising perspectives but raises questions regarding the therapy assisted by computers. To address these issues, this book intends to clarify the multidisciplinary aspects of medical engineering. The volume covers studies on the technical challenges in and barriers to the development of efficient rehabilitation and assistive technologies. It also provides a comprehensive approach to the recent advances in tele-health as a complementary medium to support the recovery process and to enhance patients' empowerment.